Prevalence of Tuberculosis Infection Among Individuals with Diabetes Mellitus at Pasir Mulya Primary Health Center, Bogor City - Damayanti, Sasti Nur; Kusdiantini, Andini (Journal of Scientific Insights, 2025)
Diabetes mellitus is a chronic metabolic disorder marked by elevated blood glucose levels and a weakened immune system, which increases vulnerability to infections such as tuberculosis. In Indonesia, the prevalence of both conditions continues to rise; however, the relationship between them remains inconsistent. This study aims to examine the association between demographic factors—specifically gender and age—and the incidence of tuberculosis among patients with diabetes mellitus. A quantitative cross-sectional study was conducted involving 30 diabetes mellitus patients registered at the Pasir Mulya Health Center, Bogor City, from September 2024 to March 2025. Tuberculosis diagnosis was performed using the GeneXpert method, while statistical analysis employed the Chi-Square test and Fisher’s Exact Test. The majority of respondents were male (66.7%) and under 60 years of age (63.3%). Statistical analysis revealed no significant association between gender (p = 0.101) or age (p = 0.702) and the incidence of tuberculosis in this population. Although a higher proportion of TB was observed in male and younger patients, the differences were not statistically significant. These findings highlight the need for sustained preventive measures and targeted health promotion, particularly among high-risk groups.